ASYMMETRIC EPOXIDATION MECHANISM OF CHALCONE USING ORGANOCATALYST AMINE DERIVATIVES OF CHINCONA ALKALOIDS BASE ON DFT METHODS - ROZA (NIM : 30510003) , DESTRIA
Compounds containing an epoxide group with certain sterechemistry are found in many bioactive natural compounds and as intermediates in many drug syntheses. Formation of these compounds can be achieved through an asymmetric catalysis of epoxidation reaction between an alkene and a peroxide. One group of the catalysts that received many attentions is primary amine derivatives of chinchona alkaloids. Evidence from laboratory experiments showed that these catalysts can make epoxides with high enantioselectivity exccess (ee). However, more studies have revealed that these reactions branch also into a peroxide, in addition to an expected epoxide formation. The branch is depended on reaction conditions, particularly on temperature and reaction time. Based on these experimental results, several mechanisms of epoxidation reactions using primary amine derivatives of chincona alkaloids have been proposed. However, to our knowledge, no reports have been found on the computational studies of these mechanisms. Based on these facts, this research is related to the computational studies on the mechanism of epoxidation reaction of ,β-unsaturated ketone derivative, namely chalcone, with an hydrogen peroxide (H2O2). The studies include four mechanism aspects, activation models of reaction, enantioselectivity, chemoselectivity, and effects of catalyst structures and substituents of the chalcone on the energy changes in the reaction coordinate. Computational analyses were performed by using density functional theory (DFT) at B3LYP level. Structures were calculated using 6-31G(d) basis set with Gaussian 09 program. These analyses were done based on a previously proposed basic mechanism of epoxidation reaction. The reaction was thought to procceed through an addition and an elimination reaction. Basic deprotonation of an hydrogen peroxide yields a hydrogen peroxide anion. Addition of this anion to an ,β-unsaturated ketone gives an β-peroxy enolat. Structure resonances of the enolat creates small negative charges on the C-, as well as on the oxygen atom. The presence of negative charges on the C- allows it to attack an oxygen atom of the weak -O-O- bond to give an epoxide ring and eliminating a hydroxide ion. The presence of a ketone conjugated with an alkene in a chalcone activates a βcarbon (C-β) with a positive charge. Reaction of the ketone with a primary amine catalyst gives an iminium ion that increase the positive charge of C-β even more due to an iminium-enamine tautomerization. In a preliminary calculation, the iminium ion formation indeed give a lowering effect on the LUMO of the system and activates the C-β. On the other hand, charge interaction in the free electron of oxygen atoms in the hyrogen peroxide increases the HOMO energy of the hydrogen peroxide anion. Thus the iminium formation becomes more preferred and soft. Tautomerization of the iminium to an enamine acrivates a further reaction step, namely a formation of a cyclic epoxide, in which a new bond is formed between C- with an oxygen atom of the peroxide. In the enamine structure the C- is more nucleophylic due to increasing of the HOMO energy. The reaction mechanisms of epoxide formation of a chalcone with an H2O2 catalyzed by a primary amine derivative of a chinchona alkaloid were evaluated based on three activation models, namely ionic model, biradikal and SOMO (Singly Occupied Molecular Orbital) models. The mechanism through an ionic activation was more posible than a mechanism via a SOMO and a biradikal mechanism. In these cases even though the ionic activation does not have a low energy barrier (ΔH), the activation energy (EA) of the addition and cyclization (ring closure) steps were lower. Moreover, the SOMO activation model required another catalyst as a radical activator. Stereocontrol of this epoxidation reaction was studied by the different of attact directions that will affect enantioselectivity. In this case hydrogen peroxide as the oxidant attack in si direction (si-face) and the direction of re (re-face). Chalcone epoxide with αR, βS configuration, will be generated the reaction was using an catalyst 9-amine(9-deoxy)quinine (QnNH2) and 9-amine(9-deoxy)epiquinidine (e-QdNH2). In the other hand chalcone epoxide with αS, βR configuration used catalysts 9-amine(9-deoxy)quinidine (QdNH2) and 9-amine(9-deoxy)epiquinine (e-QnNH2). Transition state when hydrogen peroxide binds to the double bond of chalcone (TSAB) determine the C-β configuration, whereas the cyclic formation transition state (TSBC) determine the configuration of C-α. The energy difference in the transition states and intermediates of each catalyst were about 3 to 10 kcal/mol. Overall the enantioselectivity is influenced by hydrogen bonding formation between H atom was binding with N atom of quinuclidine ring and O atom was binding C-α of chalcone, and were determined by steric control based on C8-C9 atoms of catalys and Cα-Cβ atoms of chalcone. This early transition state (TSAB) also determined the product in this reaction. This transition state produced enamine intermediate (B) or β-peroxoiminium intermediates (B1). The enamine intermediates (B) produced chalcone epoxide, while intermediates β-peroxo iminium intermediates (B1) produces β-peroxi or peroxihemikethal chalcone. Energy different (ΔH) enamine intermediates (B) was greater than β-peroxoiminium intermediates (B1). However, chalcone epoxide more stable than β-peroxo or peroksohemiketal chalcone. This is consistent with the results of previous studies, in which epoxide products were formed for a longer reaction or at a higher temperature. The results also consistent with the observation that the formation of an epoxide group preceded by a peroxohemikethal group. The prediction about functional group on the catalyst and substrate were also performed in this study. On the catalysts without methoxy group on quinoline, like chinconine CnNH2 and chinconidine, CdNH2 would raise the energy barrier of the reaction. But the enantiosectivity was accordance with catalysts wich have the same stereomer. Reduction of vinil group also did not lower the energy barrier of the reaction, as well as the addition of a methyl group to form a secondary amine. Variations of electrone withdrawing groups (EWG) and electrone donor groups (EDG) on the subsrate that EDG would lower the energy barrier at each channel. However, the presence of an EDG group, especially on A ring, raised the activation energy on anion peroxide anion addition step but decrease the activation energy on the step ring closure, so it would accelerated the formation of cyclic epoxy. In conclusion, this study has succeeded to reveal more details on the reaction mechanism of chalcone epoxidation with H2O2 catalyzed by a primary amine derivative of chincona alkaloids. In term of its activation model, ionic activation through an iminium ion formation was thought to be more reliable than radical activation models which required a co-catalyst. High energy system can be compesated by solvation energy created during the reaction take place. The enantioselectivity has been found to be related the presence of stereochemistry at C-8 of the catalyst, while chemoselectivity was created by the presence of energy differences in the transition states that leads to the epoxide or the peroxide product. This research has also able to show that the effects of structural changes of the catalyst and substituent properties in the chalcone structure on the energy changes during all reaction steps.